Constraining Ice Shelf Anisotropy Using Shear Wave Splitting Measurements from Active‐Source Borehole Seismics. Issue 9 (21st September 2020) - Lutz, Franz; Eccles, Jennifer; Prior, David J.; Craw, Lisa; Fan, Sheng; Hulbe, Christina; Forbes, Martin; Still, Holly; Pyne, Alex; Mandeno, Darcy
Abstract : Observations of ice shelf anisotropy on borehole seismic data are presented. Hot‐water‐drilledboreholes were made by the Aotearoa New Zealand Ross Ice Shelf Programme through a grounding‐line proximal site at Windless Bight and the central Ross Ice Shelf site HWD‐2. The boreholes were used to freeze seismometers into the ice at different depths. Seismic observations of shear wave splitting were made on the borehole seismometers using active sources deployed at the surface. These shear wave splitting data were used to constrain anisotropic ice crystallographic preferred orientations (CPO) within the ice column. Forward models of seismic properties from different CPO geometries are compared to the observations and a best fitting CPO model is found to explain the seismic anisotropy at HWD‐2. This model consists of a vertical girdle of ice c axes that constitute 80% of the CPO in combination with tight horizontal clusters, which contribute 20% of ice c axes. The origin of the modeled CPO is discussed with regard to calculated strain rates at the site and found to be indicative of the current shear kinematics with vertical shear plane and horizontal shear direction. At HWD‐2 the 370 m thick ice shelf is calculated to consist of at least 197 m of anisotropic ice. Key Points: Shear wave splitting is observed on active‐source borehole seismic data in two Antarctic ice shelf settings An ice CPO model is created to match these short‐pathlength observations of seismic anisotropy at one site Constraints on the vertical anisotropic ice shelf structure limit anisotropy to the deep shelf